A prospective randomised study comparing double-balloon colonoscopy and conventional colonoscopy in pre-defined technically difficult cases. Issue 5 (May 2017) - Despott, Edward J.; Murino, Alberto; Nakamura, Masanao; Bourikas, Leonidas; Fraser, Chris
Abstract: Backgrounds and aim: Technically 'difficult' (TD) colonoscopy is associated with incomplete colonoscopy, discomfort and longer procedures. Double-balloon colonoscopy (DBC) may facilitate TD colonoscopy. The primary outcome was to compare the time taken to achieve caecal intubation during conventional colonoscopy (CC) and DBC in patient with a TD colon. Methods: We performed a prospective, randomised study comparing DBC and CC for TD colonoscopy. Patients were screened for parameters predictive of TD colonoscopy using an original scoring system and randomised to DBC or CC. Pain, sedation dose, colonoscopy completeness, time taken for cecal intubation, procedure completion, recovery time and patient satisfaction were recorded. Results: Forty-four patients were recruited (DBC = 22; CC = 22). DBC facilitated total colonoscopy in 22 cases whereas 9 CC procedures were incomplete (P = 0.019). Median pre-procedure difficulty scores were equal for both groups (4.0 vs. 4.0). Mean patient discomfort, pain scores and recovery time were significantly lower for the DBC group (2.3 vs. 5.5, P = 0.001; 2.0 vs. 5.9, P = 0.005; 5 vs. 20 min, P = 0.014 respectively). Mean time taken for cecal intubation was similar (17.5 vs. 14 min, P = 0.18); Conclusion: DBC facilitates colonoscopy completion and may be a more comfortable alternative to CC for TD cases although the time taken to achieve caecal intubation was similar.